An exploration of sensory processing patterns and their association with demographic factors in healthy adults. Issue 1 (8th August 2019) - Machingura, Tawanda; Kaur, Gurjeet; Lloyd, Chris; Mickan, Sharon; Shum, David; Rathbone, Evelyne; Green, Heather
Abstract : Purpose: Previous research has provided limited evidence on whether and how demographic factors associate with sensory processing patterns (SPP) in adults. This paper aims to examine relationships between SPPs and sociodemographic factors of age, sex, education and ethnicity in healthy adults. Design/methodology/approach: A cross-sectional study design was used. A total of 71 adult participants was recruited from the community, using convenience sampling. Each participant completed the Adolescent/Adult Sensory Profile (AASP) and the Depression Anxiety Stress Scales – short version (DASS-21). Demographic information on age, sex, education and ethnicity was collected. Results were analysed using descriptive statistics and multivariate analyses of covariance (MANCOVA). Findings: SPPs, as measured by the AASP, were significantly correlated to demographic factors of age and education after controlling for emotional distress using the DASS-21. A statistically significant multivariate effect was found across the four dependent variables (low registration, seeking, sensitivity and avoiding) for the age category, F = 6.922, p = 0.009, η p 2 = 0.145, in the presence of a covariate DASS. The education category showed significance only in the seeking domain ( p = 0.008, η p 2 = 0.10) after controlling for DASS. There was no significant correlation between SPPs and gender or ethnicity. Results also indicated that mean scores of participants in this study were "similar to most people" as standardised in the AASP. Research limitations/implications: This was a cross-sectional study with limitations including that the study used a relatively small sample and was based on self-reported healthy participants. Practical implications: SPPs may correlate with healthy adults' age and to a lesser extent education. This suggests that it might be helpful to consider such demographic factors when interpreting SPPs in clinical populations, although further research in larger samples is needed to reach firmer conclusions about possible implications of demographic variables. Originality/value: The findings in this paper add to the growing evidence that suggest that SPPs vary with sociodemographic factors.